Evaluation of the expression profile of mRNAs and lncRNAs in cumulus cells associated with polycystic ovary syndrome and pregnancy - Behnaz Hammami; Fatemeh Sadat Mostafavi; Ali Akbari; Seyyed Reza Mousavi; Mohammad Kazemi (Iranian Journal of Basic Medical Sciences, 2023)
Objective(s): Polycystic ovary syndrome (PCOS), the primary cause of anovulatory infertility in women, may change the gene expression profile of cumulus cells. In human ART (assisted reproductive technology), gene expression profiling in cumulus cells, a non-invasive method, may be used to identify the most competent oocytes. We aim to identify key genes according to the network-based data and assess the suitability of these genes as markers to predict oocyte competence and PCOS diagnosis.Materials and Methods: The GSE34526 microarray dataset was obtained from the Gene Expression Omnibus (GEO) database. The function and pathway enrichment analysis for DEGs were analyzed. A protein-protein interaction (PPI) network analysis and candidate gene screening were conducted. A two-layer network consisting of mRNA and lncRNA was constructed. Expression levels of hub genes were verified using quantitative RT-PCR (qRT-PCR).Results: A total of 2721 DEGs were retained. The PPI network of selected genes associated with the biological process of “cell communication” was analyzed, and the first 10 key genes were determined by degree. Additionally, 2 hub genes and 2 hub lncRNAs, including STAT3, RHOA, GAS5, and LINC01116, were selected from the lncRNA-mRNA network. Finally, expression levels of STAT3, RHOA, GAS5, and LINC01116 were significantly increased in the cumulus cells of PCOS patients compared to the control group (P<0.05). However, there was no significant difference in expression between the pregnant and non-pregnant groups.Conclusion: STAT3, RHOA, GAS5, and LINC01116 may serve as possible diagnostic markers for PCOS. However, further studies on a larger population are needed to validate this finding.